DAMPAK TINGKAT PROFITABILITAS DAN NILAI PASAR PADA PERGERAKAN HARGA SAHAM PT. PRASIDHA ANEKA NIAGA TBK - Kussuma, Praja; Surachim, Ahim; Tanuatmodjo, Heraeni (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2016)
Purpose: This study aimed to obtain an overview of the level of profitability, market value, and stock of price in PT. Prasidha Aneka Niaga Tbk Period 2005-2014. In addition, this study aimed to obtain profitability linkage to the stock price and relation of market value to the stock price on PT. Prasidha Aneka Niaga Tbk Period 2005-2014. Design / methodology / approaches: This study used a descriptive and verification method with time series design. The statistical analysis used is multiple linear regressions. Findings: Based on the findings, it could be proved that the regression model be used to see the effect of profitability and market value of the stock price by test F. Whereas with t tests showed that the profitability of positive effect on stock prices, while the market value did not have influence to stock of price. Originality/ Value: This study could provide insight in analyzing the financial performance of the company, especially in analyzing the company's ability to generate profits, how correctly the company's value in the eyes of investors, and how well the company to increase its stock of price. Keywords: Profitability, Return on Equity, Market Value, Earnings Per Share, Stock of PriceÂ  Â